Collaboration, Creativity, and Technology: Analysis of The Needs of Innovative Models in Drama Appreciation Learning - Tato Nuryanto; Agus Nuryatin; Yusro Edy Nugroho; Indrya Mulyaningsih (Balai Bahasa Provinsi Bali, 2025)
The background of this study is based on the limitations of conventional teaching methods that are passive and do not involve students in creative practices. This study aims to explain the need for a learning model that integrates collaborative writing practices, especially in the Drama Appreciation Course. This study employs a qualitative method with a case study approach, involving 95 students from the Indonesian Language Study Program at the Syekh Nurjati State Islamic University of Cyber Cirebon. Data were collected through observation, interviews, and document analysis. The results of the study indicate that collaborative learning has been proven to enrich the process of writing drama scripts through the multidisciplinary exchange of ideas, experiments, and more complex character development. Group dynamics in collaborative writing train students in effective communication, negotiation, and conflict management. Technology integration not only facilitates the creative process but also prepares students to face the realities of the modern performing arts industry. Practical implications for institutions, the need to develop lecturer training modules, and supporting infrastructure using digital platforms or collaborative studios. Implications for the curriculum, the need to develop assessment rubrics that recognize individual contributions in teamwork. AbstrakLatar belakang penelitian ini didasari oleh keterbatasan metode pengajaran konvensional yang pasif dan kurang melibatkan mahasiswa dalam praktik kreatif. Penelitian ini bertujuan untuk mengeksplanasikan kebutuhan model pembelajaran yang mengintegrasikan praktik penulisan kolaboratif, khususnya pada Mata Kuliah Apresiasi Drama. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang melibatkan 95 mahasiswa Program Studi Bahasa Indonesia di Universitas Islam Negeri Siber Syekh Nurjati Cirebon. Data dikumpulkan melalui observasi, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa pembelajaran kolaboratif terbukti memperkaya proses penulisan naskah drama melalui pertukaran ide multidisiplin, eksperimen dan pengembangan karakter yang lebih kompleks. Dinamika kelompok dalam penulisan kolaboratif melatih mahasiswa dalam komunikasi efektif, negosiasi, dan manajemen konflik. Integrasi teknologi tidak hanya mempermudah proses kreatif, tetapi juga mempersiapkan mahasiswa menghadapi realitas industri seni pertunjukkan modern. Implikasi praktis bagi institusi, perlunya pengembangan modul pelatihan dosen dan infrastruktur pendukung dengan menggunakan platform digital atau studio kolaboratif. Implikasi bagi kurikulum, perlunya penyusunan rubrik penilaian yang mengakui kontribusi individu dalam kerja tim.